Will I publish this abstract? Determining the characteristics of medical education abstracts linked to publication - Guay, Jean-Michel; J. Wood, Timothy; Touchie, Claire; Ta, Chi Anh; Halman, Samantha (Canadian Medical Education Journal, 2020)
Background: Prior studies have shown that most conference submissions fail to be published. Understanding factors that facilitate publication may be of benefit to authors. Using data from the Canadian Conference on Medical Education (CCME), our goal was to identify characteristics of conference submissions that predict the likelihood of publication with a specific focus on the utility of peer-review ratings. Methods: Study characteristics (scholarship type, methodology, population, sites, institutions) from all oral abstracts from 2011-2015 and peer-review ratings for 2014-2015 were extracted by two raters. Publication data was obtained using online database searches. The impact of variables on publication success was analyzed using logistic regressions. Results: Of 531 abstracts with peer-review ratings, 162 (31%) were published. Of the 9 analyzed variables, those associated with a greater odds of publication were: multiple vs. single institutions (odds ratio (OR) = 1.72), post-graduate research vs. others (OR=1.81) and peer-review ratings (OR=1.60). Factors with decreased odds of publication were curriculum development (OR=0.17) and innovation vs. others (OR=0.22). Conclusion: Similar to other studies, the publication rate of CCME presentations is low. However, peer ratings were predictive of publication success suggesting that ratings could be a useful form of feedback to authors.